IMPLEMENTASI DAYA PADA ALAT PENGERING TINTA SABLON KAOS BERBASIS MIKROKONTROLER DENGAN MENGGUNAKAN THERMOCOUPLES - Junaidi Junaidi (INFO-TEKNIK, 2023)
This microcontroller-based screen printing ink dryer using a thermocouple is designed to facilitate human work and to save time for drying screen printing ink on t-shirts with plastisol ink. The process used by home convection usually still uses a manual screen printing ink dryer which takes about 7 minutes for the drying process. In order to overcome this problem, a microcontroller-based screen printing ink dryer is needed which can dry screen printing ink automatically. In this tool there is a display that displays voltage and current, therefore researchers can find out the amount of power obtained on this tool. The results of measuring the electric power on the screen printing ink dryer based on this microcontroller have a maximum power of 1148 watts, the results of measuring the electric power have an accuracy of 93.1%. A good temperature for drying screen printing ink using this tool is 170˚C and the drying process takes 3 minutes. In the September 2022 study, with a total order of 1,670 screen prints, it was recorded that the average usage was 2 hours and 30 minutes per day, so the amount of electrical energy used was 74.22 kWh. Compared to using a hot gun, this tool is much faster to work on and more cost-effective to use Keywords: Screen Printing, Electrical Power, T-shirts, Plastisol, Heater